2003
DOI: 10.1177/153537020322801023
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Thermal Therapy in Lifestyle-Related Diseases

Abstract: Systemic thermal therapy, such as taking a warm-water bath and sauna, induces systemic vasodilation. It was found that repeated sauna therapy (60 degrees C for 15 min) improved hemodynamic parameters, clinical symptoms, cardiac function, and vascular endothelial function in patients with congestive heart failure. Vascular endothelial function is impaired in subjects with lifestyle-related diseases, such as hypertension, hyperlipidemia, diabetes mellitus, obesity, and smoking. Sauna therapy also improved endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 43 publications
1
75
0
3
Order By: Relevance
“…This suggests that using sauna sessions did not contribute to changes in the content of adipose tissue in the men studied. In a study by Biro et al [28], who used far infrared-ray dry sauna with the temperature of 60°C, the researchers have demonstrated that 15-min sauna sessions (after which the patients remained covered with blankets for 30 min in order to maintain the core temperature elevated by 1°C) repeated for 2 weeks contribute to body mass reduction, decrease in blood pressure and glucose levels in the people with diagnosed diseases of affluence. However, postsession changes in lipid profile in the above study failed to be statistically significant [28].…”
Section: Ijomeh 2014;27(4) 614mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that using sauna sessions did not contribute to changes in the content of adipose tissue in the men studied. In a study by Biro et al [28], who used far infrared-ray dry sauna with the temperature of 60°C, the researchers have demonstrated that 15-min sauna sessions (after which the patients remained covered with blankets for 30 min in order to maintain the core temperature elevated by 1°C) repeated for 2 weeks contribute to body mass reduction, decrease in blood pressure and glucose levels in the people with diagnosed diseases of affluence. However, postsession changes in lipid profile in the above study failed to be statistically significant [28].…”
Section: Ijomeh 2014;27(4) 614mentioning
confidence: 99%
“…In a study by Biro et al [28], who used far infrared-ray dry sauna with the temperature of 60°C, the researchers have demonstrated that 15-min sauna sessions (after which the patients remained covered with blankets for 30 min in order to maintain the core temperature elevated by 1°C) repeated for 2 weeks contribute to body mass reduction, decrease in blood pressure and glucose levels in the people with diagnosed diseases of affluence. However, postsession changes in lipid profile in the above study failed to be statistically significant [28]. The present study found a statistically significant decline in total cholesterol levels compared to the initial values measured directly after the 1st sauna session and then after the last sauna session and 24 h after completion of the sessions.…”
Section: Ijomeh 2014;27(4) 614mentioning
confidence: 99%
“…These results could be related to the promising effect of sauna therapy for patients with diabetes and other life-style diseases [61], as well as with the helpful hottub therapy for diabetic patients [62] and diabetic rats [63]. Moreover, Kokura et al [7] found that whole body hyperthermia (WBH) may provide a new therapeutic or preventive modality against obesity-related diseases such as type 2 diabetes mellitus and metabolic or insulin resistance syndrome [8].…”
Section: Discussionmentioning
confidence: 99%
“…Because HSP72 protects cells in part by suppressing the JNK and/or NF-kB activity, decreased expression of HSP72 under such conditions could cause a vicious cycle [15]. Obese subjects also showed a decrease in fasting blood glucose after sauna therapy for 2 weeks, 15 min/day at 60°C [16]. These reports together with our animal studies mentioned above encouraged us to apply MES ?…”
Section: Increased Expression Of Hsp72 Ameliorates Insulin Resistancementioning
confidence: 99%